PERTANGGUNGJAWABAN KORPORASI DALAM TINDAK PIDANA KORUPSI PENGADAAN BARANG DAN JASA PEMERINTAH (Suatu Penelitian di Wilayah Hukum Pengadilan Tipikor Banda Aceh) - Ibsaini Ibsaini; Mahdi Syahbandir (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2018)
This research examines a corporation responsibility in the corruption of governmental goods and services procurements. This research applies juridical empirical approach. In accordance with the Act of Corruption Suppression, the liability of the corruption cases of corporation is also involves its corporation regarding the corruption. Pursuant to Article 20 (1) in terms of the corruption committed by and over the name of a corporation, the charges and sentences can be impose toward the corporation and its administrators. However, at the Court for Corruption in Aceh (2013-2017), there are 36 cases of corruptions committed by the corporations that have never been held liable on them, meaning that the corporation has never been convicted due to the commission. This research is purposed to know the forms of corruption committed by corporations at the Court for Corruption in Banda Aceh, reasons for not being held the corporations liable for the corruption, and legal impact that might rise if the corporations are not held liable for corruption.